COMPARISON OF EFFICACY OF CHEMO-MECHANICAL CARIES REMOVAL (CARISOLV) WITH THAT OF CONVENTIONAL DRILLING METHOD. - Dr Seema Kamble; Dr M P Puranik; Dr Soumya K R; Dr Ashwini Biradar (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Introduction: Dental procedures are frequently linked to discomfort and anxiety due to the use of high and low speed drills. The objective of the study was to evaluate the clinical effectiveness of chemo-mechanical caries removal using Carisolv and compare it with conventional caries removal methods (drilling technique)Materials and Methods:  A total of 50 children between the ages of 9 and 12, who had cavities bilaterally and affecting only the dentine but not affecting the pulp, were selected. The removal of caries was accomplished using conventional drilling techniques or by employing carisolv. A gel was used to apply over the decayed dentine, and the softened decay was carefully eliminated using specifically specialised hand instruments. A cavity's caries-free status was determined by an independent assessor using clinical criteria.Results: The results indicate that the caries removal using the carisolv method was highly effective, with a success rate of 94%. The average duration for caries removal using carisolv is 7 ± 2.40. According to a verbal rating scale, 66% of participants reported experiencing no discomfort when using carisolv. The children found the scent and taste sensations to be satisfactory and acceptable. CONCLUSION: Carisolv successfully removes caries without causing discomfort.The Chemo-Mechanical Caries Removal by carisolv is acceptable and more comfortable for patients, reducing pain, anxiety with no requirement for a local anaesthetic. This could be considered as a potential alternative treatment modality.